Gliotransmission and adenosinergic modulation: insights from mammalian spinal motor networks - Acton, David (J Neurophysiol, 2017)
Astrocytes are proposed to converse with neurons at tripartite synapses, detecting neurotransmitter release and responding with release of gliotransmitters, which in turn modulate synaptic strength and neuronal excitability. However, a paucity of evidence from behavioral studies calls into question the importance of gliotransmission for the operation of the nervous system in healthy animals. Central pattern generator (CPG) networks in the spinal cord and brain stem coordinate the activation of muscles during stereotyped activities such as locomotion, inspiration, and mastication and may therefore provide tractable models in which to assess the contribution of gliotransmission to behaviorally relevant neural activity. We review evidence for gliotransmission within spinal locomotor networks, including studies indicating that adenosine derived from astrocytes regulates the speed of locomotor activity via metamodulation of dopamine signaling.